The effect of biomass, operating conditions, and gasifier design on the performance of an updraft biomass gasifier - James Rivas, Arthur Mc Carty (Kansas State University, 2012)
Gasification is an efficient way to produce energy from biomass, which has significant positive impacts on the environment, domestic economy, national energy security, and the society in general. In this study, a lab-scale updraft biomass gasifier was designed, built, and instrumented for stable gasification using low-bulk density biomass. Related accessories, such as a biomass feeder, inlet air temperature controller, air injection nozzle, and tar cracking system, were also developed to enhance gasifier performance. The effect of operation parameters on gasifier performance was studied. Two operational parameters, including air flow rate and feed-air temperature, were studied on three sources of biomass: prairie hay, sorghum biomass, and wood chips. Results showed that higher air flow rate increased tar contents in syngas for all three types. It was also found that different biomasses gave significantly different tar contents, in the order of wood chips>sorghum biomass>prairie hay. Feed-air temperature did not have a significant effect on tar content in syngas except for prairie hay, where higher feed air temperature reduced tar. A statistical model was implemented to study differences on syngas composition. Results showed that different biomasses produced syngas with different high heating value, e.g., wood chips > prairie hay > sorghum biomass. CO composition also showed differences by feed air temperature and biomass, e.g. prairie hay>wood chips>sorghum biomass, but H[subscript]2 did not show significant differences by either biomass type or operating conditions. Moreover, because of the downstream problems caused by tars in syngas such as tar condensation in pipelines, blockage and machinery collapse, an in-situ tar cracking system was developed to remove tars in syngas. The tar cracking device was built in the middle of the gasifier’s combustion using gasification heat to drive the reactions. The in-situ system was found to be very effective in tar removal and syngas enhancement. The highest tar removal of 95% was achieved at 0.3s residence time and 10% nickel loading. This condition also gave the highest syngas HHV increment of 36% (7.33 MJ/m[superscript]3). The effect of gas residence time and Ni loading on tar removal and syngas composition was also studied. Gas residence of 0.2-0.3s and Ni loading of 10% were found appropriate in this study.
Keywords: Biomass gasification; Tar cracking; Gasification parameters; Syngas reforming; Alternative Energy (0363); Energy (0791)